The Effect of Customer Satisfaction and Relationship Marketing on Loyalty of Honda Motorcycle and Car Customers at PT. Internusa Tribuana Citra Multifinance Medan - Yovie Ernanda (Jurnal Mantik, 2021)
The purpose of this study is to test and analyze the effects of customer satisfaction on customer loyalty at car and motorcycle leasing at PT. Internusa Tribuana Citra Multi Finance Medan; to test and analyze the effect of relationship marketing to the loyalty of customers of leasing cars and motorcycles at PT. Internusa Tribuana Citra Multi Finance Medan; as well as to test and analyze the effects of customer satisfaction and relationship marketing on customer loyalty leasing cars and motorcycles at PT. Internusa Tribuana Citra Multi Finance Medan. This research used a quantitative approach. The research populations were 125 customers who had taken the leasing services of the company more than once and the data taken were the subscribers recorded in December 2016. There were 30 customers from the population for pretest validity test and reliability of the research instrument the remaining 95 customers for analysis data. The results of this study indicate that partially, customer satisfaction has a significant and positive effect on customer loyalty at PT. Internusa Tribuana Citra Multi Finance Medan. Partially, relationship marketing had a positive and significant effect on customer loyalty at PT. Internusa Tribuana Citra Multi Finance Medan. Simultaneously, customer satisfaction and relationship marketing had a positive and significant effect on customer loyalty at PT. Internusa Tribuana Citra Multi Finance Medan. Customer loyalty was simultaneously affected by customer satisfaction and relationship marketing up to 0.354 or 35.4% and the remainings 64